THERMOELECTRIC DEVICE FOR INTRACAVITARY HYPOTHERMIA - T. A. Ismailov; O. V. Evdulov; M. A. Khazamova; T. A. Ragimova; R. A.-M. Magomadov (Вестник Дагестанского государственного технического университета: Технические науки)
Objectives In this research, we aimed to develop a thermoelectric device (TED) for intracavitary hypothermia, to carry out experimental studies into its functional characteristics, as well as to develop treatment procedures using this device.Method A TED design for intracavitary hypothermia was developed, consisting of two thermoelectric batteries (TEBs) interconnected using an allmetal heat pipeline equipped with an influencing applicator and a liquid heat exchanger. Experimental studies of the device were carried out on a designed bench, which included a climatic chamber, a source of electrical energy and a temperature meter connected to a PC. Results Temperature changes at the control points of the device were recorded over time. Changes in the time taken to stabilise temperatures of the device tip, heat pipe and heat sink system at different TEB supply currents were investigated. Possible methods for treating some ENT diseases using the developed device are described.Conclusion It is shown that the temperature of the applicator is stabilised after approximately 4-4.5 minutes without load. At the same time, an increase in the current of the additional TEB from 5 to 12 A at the main TEB current of 23 A reduces the temperature from 237 K to 224 K. In the process of carrying out the procedures, the necessary level of a decrease in the temperature of a biological object can be reached at the supply current of the main and additional TEBs equal to 23 and 12 A, respectively, after 2.5 minutes. The full potential of the TED device will be realised through the developed of methods for treating ENT diseases.